If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(Y + 9) + 3Y = 30 Reorder the terms: 3(9 + Y) + 3Y = 30 (9 * 3 + Y * 3) + 3Y = 30 (27 + 3Y) + 3Y = 30 Combine like terms: 3Y + 3Y = 6Y 27 + 6Y = 30 Solving 27 + 6Y = 30 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 6Y = 30 + -27 Combine like terms: 27 + -27 = 0 0 + 6Y = 30 + -27 6Y = 30 + -27 Combine like terms: 30 + -27 = 3 6Y = 3 Divide each side by '6'. Y = 0.5 Simplifying Y = 0.5
| 10+6a=-104 | | f(x)=3x^2+5x+7 | | X/2-430 | | 2(t+8)=8 | | 9x-6=7y+3x | | 5y+6q=20 | | 200+.62x=379.8 | | 4x^2-10x-126=0 | | 2x-x=-1+3 | | 200-.62x=379.8 | | 24a^3b^2-16a^2b^3/8ab | | 5y-8/8-5y | | 5(4a+3b)5(2a+3b)= | | 2/5x-1-9/4x-6 | | 25x-21=16x-4x | | 3(y+9)1y=30 | | (2x-5)/(x-1)3 | | sin(2x)-(.259)=cos(x)-(.978) | | Y=-x/4-3 | | 9(t+5)=5 | | 6x^2+4x+7=7 | | (2x-5/x-1)3 | | -3d=36 | | 7+ax-9=-6 | | X-2/5=3.5 | | (2h-3i)(h+4i)= | | 71.4=6(m+3.6) | | 2(3(1.6)+2)=2x-1+x | | 2(x-4)+1x=10 | | 2x+x+2=5 | | y=3.6x-7.1 | | x+1=x^2+5x-2 |